Incorporation of Standard Operating Procedures for Leadership and Volunteer Transitions in a Student-Run Free Clinic - Jagadish, Ishitha; Modi, Neal (Journal of Student-Run Clinics, 2022)
At the Saint Louis University Health Resource Center, all student leadership roles transition yearly, requiring a robust method to maintain institutional knowledge. Standard operating procedures (SOPs) are written documents containing detailed instructions for the completion of functions within a greater organization. SOPs are utilized in clinical settings and may be useful for student-run free clinics (SRFCs). This project sought to formally establish clinic procedures into centralized documents and assess the utility of these documents. We created SOPs for all leader and volunteer positions which were then assembled into Leadership and Volunteer Handbooks for increased accessibility. Two surveys, one for leaders and one for volunteers, were distributed after the 2020-2021 leadership transition period to investigate the utility of the SOPs. Although the response rates were insufficient, results suggest that leader and volunteer respondents found confidence in utilizing the SOPs during the transition period and beyond. SOPs allow our volunteers and leaders to enhance the performance of their roles despite frequent turnover of positions. Per constructive feedback from survey respondents, we plan to improve awareness of SOPs and increase the frequency of updating SOPs to reflect current clinic operations. Future research should evaluate the utility and efficacy of SOPs in other SRFCs through multiple transition cycles of active leaders and volunteers.